Clinical Evaluation of Serological Diagnostic Assays for COVID-19 Antibody Detection - Hijab Batool, Muhammad Dilawar Khan, Omar Rasheed Chughtai, Akhtar Sohail Chughtai, Shakeel Asharf, Saqib Shahzad (Journal of Islamic International Medical College)
Objective: This study was aimed to evaluate the laboratory performance of three different serological assays(Immuno fluorescence Assay (IFA), Electrochemiluminescence Immunoassay (ECLIA) and Chemiluminescent Microparticle Immunoassay (CMIA) to see if they performed accurately according to the manufacturers' claims. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at Chughtai Institute of Pathology from 01st April to 30th May 2020. Materials and Methods: Blood samples were collected from 75 adult male and female patients, 25 were pre pandemic samples and 50 were diagnosed cases of COVID-19 in whom sample was taken 21 days after they showed up symptoms. All cases were analyzed to detect the presence or absence of COVID-19 IgG antibodies using Immunofluorescence assay (IFA), electrochemiluminescence immunoassay (ECLIA) and Chemiluminescent Microparticle Immunoassay (CMIA). SPSS 23.0 and EP evaluator were used to assess sensitivity, specificity and Cohen's kappa. Results: The study compares the effectiveness of three diagnostic methods (ECLIA, CMIA, and IFA) against PCR for detecting COVID-19 antibodies using Cohen's Kappa statistics. ECLIA showed the highest agreement with PCR (Kappa 0.748), followed by CMIA (Kappa 0.602), and IFA (Kappa 0.564), indicating that ECLIA is the most reliable method for detecting both positive and negative cases. The findings suggest variability in accuracy across these methods, with ECLIA being the most consistent. Conclusion: Detection of anti-SARS-CoV-2 antibodies may act as a reliable diagnostic tool provided the assay is properly validated before use. Chemiluminescence immunoassay proves to be a better serological assay as compared to Electrochemiluminescence and Immunofluorescence assay.